Evaluating the effect of chlorhexidine mouthwash 0.2% in controlling the oral complications of chemotherapy - M. Sahebjamee; M. Jahani; F. Khalili (Tehran University of Medical Sciences, 1996)
In order to evaluate the effect of chlorhexidine mouthwash in controlling oral complications of chemotherapy, 146 patients were recruited among the patients referred to heamatology department of Shariati hospital who were under treatment by routine chemotherapic drugs like EBDV, CMF or FU-Lucoverin5 for first, second or third time. The patients were  allocated into two groups to receive either chlorhexidine or Placebo  for a week after careful examination and evaluation. Finally, It was concluded that Chlorhexidine is effective to reduce oral complications of chemotherapy (P-value≤0.002).